Direct and Indirect Probes for Composite Dark Matter - Khlopov, Maxim Y. (Frontiers in Physics, 2019)
Dark matter candidates are one of the profound signatures of new physics, reflecting existence of new stable particles. If such particles are charged they can bind with ordinary electrons, forming anomalous isotopes. Severe constraints on the anomalous hydrogen exclude new stable single charged particles, but the case of stable double charged particles is not excluded so easily. Similar to ordinary baryonic matter dark matter candidates can be in the form of neutral dark atoms in which new stable or sufficiently long living double charged particles are bound by ordinary Coulomb interaction. In the most simple case only negative double charged particles are bound in O-helium (OHe) dark atoms with primordial helium. OHe hypothesis can provide the solution for puzzles of direct dark matter searches by specifics of OHe interaction in the matter of underground detectors. OHe interaction in the matter can lead to formation of various exotic forms of O-nuclearities. Provided that the mass of the double charged particle is around 1.25 TeV OHe hypothesis can explain the observed positron annihilation line excess in the galactic bulge by pair production in de-excitation of OHe atoms colliding in this region. In the model of Walking Technicolor generation of primordial excess of negatively charged techniparticles (over their antiparticles) can be related to the baryon asymmetry of the Universe, giving proper relationship of baryonic and non-baryonic matter densities. Such primordial excess may be accompanied by a subdominant excess of longliving positively double charged techniparticles, whose decay to same sign pair of leptons can explain the high energy cosmic positron anomaly, detected by PAMELA and AMS02. This explanation should be confronted with the cosmic gamma ray background measured by FERMI/LAT, what put upper limit on the mass of a decaying double charged particle. It makes search for stable double charged particles at the LHC a direct probe for composite dark matter hypothesis.